2010
DOI: 10.5751/es-03162-150109
|View full text |Cite
|
Sign up to set email alerts
|

Beyond Roadkill, Radiotracking, Recapture and FST—a Review of Some Genetic Methods to Improve Understanding of the Influence of Roads on Wildlife

Abstract: 2010. Beyond roadkill, radiotracking, recapture and F ST -a review of some genetic methods to improve understanding of the influence of roads on wildlife. Ecology and Society 15(1): 9. [online] URL: http://www.ecologyandsociety.org/vol15/iss1/ art9/

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
39
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 34 publications
(40 citation statements)
references
References 103 publications
0
39
0
1
Order By: Relevance
“…It is worth noting that moderate to low crossing rates may not necessarily imply functional connectivity (Riley et al 2006). This type of information is logistically difficult to obtain using other than genetic methods (Clevenger and Sawaya 2010;Simmons et al 2010). Because the impact of railways is relatively recent, highly variable markers such as microsatellites are the most suitable method for estimating demographic and population genetic effects.…”
Section: Indirect Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…It is worth noting that moderate to low crossing rates may not necessarily imply functional connectivity (Riley et al 2006). This type of information is logistically difficult to obtain using other than genetic methods (Clevenger and Sawaya 2010;Simmons et al 2010). Because the impact of railways is relatively recent, highly variable markers such as microsatellites are the most suitable method for estimating demographic and population genetic effects.…”
Section: Indirect Methodsmentioning
confidence: 99%
“…For instance, Clevenger and Sawaya (2010) showed that the passive hair-collection methods based on barbed wire and/or adhesive strings, followed by microsatellite analyses, was an effective technique for monitoring wildlife pass use at an individual level for cougars (Puma concolor), and black and brown bears in Canada. Furthermore, as costs for genetic analyses are become lower, the sample sizes have increased in recent studies (Simmons et al 2010). The main limitation of this method is that it is only suitable for large animals whose remains (hairs, feathers, scats) can be found in the field in sufficient quantity to extract DNA from them.…”
Section: Direct Methodsmentioning
confidence: 99%
See 3 more Smart Citations